Nanohyperthermia of malignant tumors.i. lanthanum-strontium manganite magnetic fluid as potential inducer of tumor hyperthermia - Solopan, S.; Belous, A.; Yelenich, A.; Bubnovskaya, L.; Kovelskaya, A.; Podoltsev, A.; Kondratenko, I.; Osinsky, S. (Experimental Oncology, 2011)
Objectives: To synthesize magnetic particles of lanthanum-strontium manganite, prepare the magnetic fluid (MF), evaluate the generation of heat by particles and determine their common toxiсity. Methods: Nanoparticles based on the solid solutions of lanthanum-strontium manganite (La1-xSrxMnO3) have been synthesized by a sol-gel method. Conventional methods of experimental oncology were used. Results: Nanoparticles of ferromagnetic materials on the basis of solid solutions of lanthanum strontium manganite by sol-gel method were synthesized. It was shown the possibility to regulate the aggregate form of particles that are formed during the synthesis. Magnetic fluid based on the synthesized nanoparticles and water solutions of agarose have been produced. It was shown the possibility to heat this magnetic fluid up to 42–45 °С in externally applied alternating magnetic field (AMF) operated at 100–400 kHz. It was determined that under long-term influence of AMF nanofluid is heated up to temperature which is not over that of magnetic phase transition. It was detected that magnetic powder as well as fluid have not displayed acute toxicity or side effects (intraperitoneal or intratumoral administration) in animals either intact or with transplanted tumors. Conclusions: Possibility of synthesized magnetic fluid to generate heat in externally applied AMF as well as lack of side effects allow to consider its as a potential mean for tumor hyperthermia (HT).